PERAN POLA KOMUNIKASI ANTARBUDAYA DALAM MENCEGAH KONFLIK ANTAR KELOMPOK AGAMA - Rizak, Mochamad (Islamic Communication Journal, 2018)
Intercultural communication becomes a norm in the midst of society that has been globalized. There are no more regional boundaries and cultural barriers that travel between one person and another. But in reality, cultural differences often cause ripples of problems and even lead to the emergence of social conflict. This is due to the strengthening of ethnic identity that led to the emergence of ethnocentrism and stereotype in which one group feels superior to other ethnic groups.This study discusses the relationship of communication and culture that is like two sides of the coin. Culture shapes human thoughts and behavior and shapes our patterns of communication. While with communication we can convey the result of creation, desire and taste to others. This study wanted to examine matters relating to intercultural communication, especially on religious groups that led to the emergence of prejudice, causing a sense of mutual suspicion and even hostility between religious groups. In this case prejudice becomes an obstacle in communicating.Intercultural communication aims to remove barriers as a result of cultural differences. As the principle of communication that the more like the cultural background will be more effective communication. Intercultural communication wants to make us human beings, ie people who look at others from the point of their culture not from the point of our culture so that will grow mutual respect.Keywords: communication, culture, religious group————————————————————————————Komunikasi antar budaya menjadi norma di tengah-tengah masyarakat yang telah mengglobal. Tidak ada lagi batas-batas regional dan hambatan budaya yang bergerak antara satu orang dan yang lain. Namun dalam kenyataannya, perbedaan budaya sering menyebabkan riak masalah dan bahkan mengarah pada munculnya konflik sosial. Hal ini disebabkan menguatnya identitas etnis yang menyebabkan munculnya etnosentrisme dan stereotipe di mana satu kelompok merasa lebih superior dari kelompok etnis lain.Studi ini membahas hubungan komunikasi dan budaya yang seperti dua sisi mata uang. Budaya membentuk pikiran dan perilaku manusia dan membentuk pola komunikasi kita. Sementara dengan komunikasi kita dapat menyampaikan hasil ciptaan, keinginan dan rasa kepada orang lain. Penelitian ini ingin meneliti hal-hal yang berkaitan dengan komunikasi antar budaya, terutama pada kelompok agama yang menyebabkan munculnya prasangka, menyebabkan rasa saling curiga dan bahkan permusuhan antar kelompok agama. Dalam hal ini prasangka menjadi kendala dalam berkomunikasi.Komunikasi antarbudaya bertujuan untuk menghilangkan hambatan sebagai akibat dari perbedaan budaya. Sebagai prinsip komunikasi yang lebih menyukai latar belakang budaya akan komunikasi yang lebih efektif. Komunikasi antarbudaya ingin menjadikan kita manusia, yaitu orang yang melihat orang lain dari sudut budaya mereka bukan dari sudut budaya kita sehingga akan tumbuh saling menghargai.Kata kunci: komunikasi, budaya, kelompok keagamaanÂ